Purple healing rays and paralysis: Intersections of disability and gender theory in comics. (1st March 2019) - Bryan, Peter Cullen
Batgirl is the exception to the rule of disability as needing to be overcome in superhero comics. Barbara Gordon stands out among comic book characters because her injuries last, whereas most male superheroes do not sustain lasting injuries. Through a history of the character Barbara Gordon/Batgirl/Oracle and her reception in the Batman comic fandom, this article explores how disabled bodies and women's bodies are treated in comic books and in the fandom. Gordon's importance to the community of disabled fans is at times in conflict with the messages received about Gordon's role as a female character who sustained her injury as part of a plotline for a male character in The Killing Joke. Gordon may be the exception to the treatment of disabled characters, but her treatment in The Killing Joke fits into a long history of injuring or killing women in service of men's plots. Gordon's treatment from comic writers and critics is examined through the lens of disability and gender studies, as is the sense of loss that her rewriting created in the fandom.